Se–C bond and reversible SEI in facile synthesized SnSe2⊂3D carbon induced stable anode for sodium-ion batteries. (20th March 2020) - Yang, Kaiwei; Zhang, Xixue; Song, Keming; Zhang, Jiyu; Liu, Chuntai; Mi, Liwei; Wang, Yingying; Chen, Weihua
Abstract: Metal selenides have gained great attention and are considered as one of promising anode materials for resource-abundant sodium-ion batteries, due to their high capacity and higher reaction kinetics. However, poor cycling hinders their practical applications. To solve the issue, effective combining rationally designed functional carbon architecture and metal selenides is advanced expectedly, yet complex routines are inevitable and severely impede further engineering production. Herein, with a facile, environmental-friendly, easy-scalable integrated carbo-thermal method, SnSe2 nanoparticles are well-embedded in 3D porous carbon (SnSe2 ⊂3DC). The inherent Se–C bond and electrochemically formed reversible solid electrolyte interphase cooperating with the buffering 3D porous structure successfully endow stable structure and high reversible conversion and alloying reactions. As a result, the obtained SnSe2 ⊂3DC delivers excellent capacity of 340 mAh g −1 without decay after 170 cycles at high current density of 2.5 A g −1 . The full cell SnSe2 ⊂3DC//NaFePO4 was assembled to confirm its applications. This work could not only provide easy-scalable high-performance anode for SIBs applications but also open avenue to promote other electrode materials.